Nanoporous Cu2O nanotube/nanorod array electrodes for non-enzymatic glucose sensing with high sensitivity and very low detection limit - Jayasingha, Lakmini; Jayathilaka, Charith; Kumara, Roshantha; Ohara, Koji; Kaumal, Migelhewa; Gunewardene, Siyath; Dissanayake, Dhammike; Jayanetti, J. K. D. S. (My University, 2020)
This study compares the non-enzymatic glucose sensing performance by Cu2O nanorods/nanotubes grown using electrochemically anodized Cu foam and Cu plates to form binder free one-dimensional Cu(OH)2 nanostructures which were subsequently annealed at higher temperatures. Resulting Cu2O nanorods/nanotubes had diameters between 100 and 200 nm and lengths in excess of 10 mm. The surface morphology and structure of these thin films studied using scanning electron microscopy, X-ray diffraction and energy dispersive X-ray spectroscopy showed that the copper foam based Cu2O structures consisted of nanotubes/nanorods distributed over entire 3-dimensional space containing dense nano pores of size ~20 nm on outer surfaces. Cu plate based nanorods consisted of grooved macaroni type surface morphologies. Non-enzymatic glucose sensing made using chronoamperometric and cyclic voltammetric measurements showed that the Cu2O/Cu foam electrodes had a high sensitivity of 5792.7 mA mM 1 cm 2 , a very low detection limit of 15 nM (S/N ¼ 3), multi-linear detection ranges of 15 nMe0.1 mM and 575e4098.9 mM with a faster response time of less than 1 s. Cu plate based nanorods showed a sensitivity of 141.9 mA mM 1 cm 2 , with a lower detection limit of 510 nM (S/N ¼ 3). The significantly high sensitivity of Cu2O/Cu foam electrodes is attributed to the availability of increased amount of active sites due to the large effective surface area provided by Cu2O nanorods/nanotubes. The study also demonstrates the influence of the substrate on surface morphology of the nanorods/nano tubes. These Cu foam based Cu2O electrodes provide a promising platform for non-enzymatic glucose detection with high specificity and reproducibility.
Keywords: Electrochemical anodization; Nanoporous Cu2O nanotubes/nanorods; chronoamperometry; Sensitivity; Detection limit